Distribution and speciation of copper in rice (Oryza sativa L.) from mining-impacted paddy soil: Implications for copper uptake mechanisms. (May 2019) - Cui, Jin-li; Zhao, Yan-ping; Lu, Ying-Jui; Chan, Ting-shan; Zhang, Li-li; Tsang, Daniel C.W.; Li, Xiang-dong
Abstract: Long term mining activities can cause significant metal pollution in the environment, thereby showing potential risk to the paddy field. Elucidating the interfacial processes of trace metals from contaminated paddy soil to rice within the rhizosphere can provide important information on metal biogeochemistry and food safety. The current study aims to explore the spatial distribution and molecular speciation of Cu from rhizosphere to rice plant in a mining-impacted paddy soil, and reveal the possible uptake mechanisms. X-ray absorption near edge structure (XANES) analysis indicated that Cu was primarily associated with iron oxide and sulfide in soil with a minor proportion of organic complexed species. In the rice samples, Cu showed much higher concentrations in the roots than the shoots, as most Cu was sequestered in the root surface and epidermis (primarily in the form of C/N ligands bound Cu species), rather than root xylem, as identified by micro X-ray fluorescence (μ-XRF) imaging coupling with μ-XANES. By contrast, in the root xylem, thiol-S bound Cu(I) complex was observed, representing the reduced product of Cu(II) by thiol-S ligands in rice root. The absorbed Cu was probably transported from the root to the aerial part as C/N ligand bound Cu complex such as Cu-histidine like species, which was observed in the root xylem. The large retention capacity and reduction of Cu(II) in rice root alleviated Cu toxicity to rice, which was beneficial for food safety (e.g., lower concentration of Cu in rice grains). These findings showed for the first time that the uptake mechanisms by rice from field contaminated sites, which shed light on Cu detoxification process and potential remediation strategies. Graphical abstract: Unlabelled Image Highlights: The distribution and speciation of Cu from rhizosphere to rice plant was investigated in a mining-impacted paddy site. Much higher Cu was observed in roots than shoots, and most Cu was sequestered in root surface and epidermis as Cu-alginate. Direct observation of Cu(I) complexed with thiol-S ligands on root epidermis and xylem indicated Cu reduction by rice plant.